Diabetic Foot Ulcer (DFU) Gene Expression in Homo Sapiens Species - Wulandini Putri, Adquinta; Azminah, Azminah (Riviera Publishing, 2023)
Diabetic foot ulcer (DFU) is a major problem in people with diabetes because more than 15% of patients have to treat DFU during their lifetime. 1 out of people with diabetes can experience a diabetic foot ulcer (DFU). At least a quarter of diabetic foot ulcer (DFU) sufferers cannot recover completely. The prevalence of diabetic foot ulcers (DFU) in Indonesia reaches 8.7%. The current DFU treatment approved by the FDA uses Becaplermin, a recombinant platelet-derived growth factor derivative. However, this treatment has a weakness in systemic bioavailability. FAgene expression analysis method is needed. to develop other therapies. This article aims to discover specific genes that play a role in diabetic foot ulcer (DFU) wound healing. In this systematic review, we searched the GEO Data Sets database to identify articles published from 2018 to 2023. The search results for DFU gene expression data for all species obtained 130 articles. Then, the DFU gene expression data series of Homo sapiens species was filtered to obtain ten related articles. This research has implications in providing better insight into the specific genes involved in the healing process of DFU wounds. This research also has the potential to contribute to early diagnosis of DFU injuries and better treatment.